UMP UTPs strategic collaboration in research development best practices and academic excellence - Mimi Rabita, Abdul Wahit (2023)
SERI ISKANDAR, 16 February 2023 - The meeting between Universiti Malaysia Pahang (UMP) and Universiti Teknologi Petronas (UTP) provided an opportunity for both parties to share expertise in academics, learning, research development, human resources, student development and financial sustainability.